Understanding the materialist method historical-dialectic - Orth, Miguel Alfredo (Sofia, 2026)
At the present article we seek to problematize professor Triviños Preliminary Document, that was used at his Search Methodology classes. This document, named Introduction to Dialectical Method at Social Science Search was organized by Professor Augusto Nibaldo Silva Triviños, aiming helping the neophytes of postgraduate studies at qualified search. In this article, we objectively present and discuss the dialectical method of four theorists who discuss Karl Marx’s dialectical method. Methodologically we work with literature review of the field, as well we seek to undestand, discuss and work with the Dialectical Search Method. Regarding the results, it is worthy highlight that the authors studied (Hegel, Cheptulin, Kosik Triviños) revealed to use qualitative research methodologies, however, they all present and discuss specific aspects and issues of Qualitative Methodology. Triviños, however, aimed to collaboratively think and write during his methodological path, as well as he guided his neophytes to develop their search based on the Materialist Method Historical-Dialectic, that seeks to prioritize the study of material and qualitative phenomena of the Materialist Historical-Dialectic, furthermore request to identify the main and secondary categories and experience the connection between what is done and what is researched, among other aspects of the dialectical method.